2020
DOI: 10.1097/sla.0000000000004242
|View full text |Cite
|
Sign up to set email alerts
|

Locoregional Residual Esophageal Cancer after Neo-adjuvant Chemoradiotherapy and Surgery Regarding Anatomic Site and Radiation Target Fields

Abstract: Objective:Neoadjuvant chemoradiotherapy followed by surgery establishes a considerable pathologic complete response (pCR) in EC. The aim was to determine site of residual tumor and its prognostic impact.Summary Background Data:High rates of residual tumor in the adventitial region even inside the radiation fields will influence current decision-making.Methods:We evaluated resection specimens with marked target fields from 151 consecutive EC patients treated with carboplatin/paclitaxel and 41.4Gy between 2009 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Regarding the tumor residual pattern in the primary tumor, the dominant pattern in this study was diffuse remnant, followed by shallow remnant, central remnant, and deep remnant. Residual tumor cells were commonly present in adventitia, which is similar to the findings of recent studies on esophageal cancer treated with NCRT, which mostly comprised patients with esophageal adenocarcinoma (28). However, this finding is inconsistent with an observation made in a previous study, which reported that the mucosa and submucosa of the esophageal wall are commonly affected after chemoradiotherapy for esophageal cancer (29).…”
Section: Discussionsupporting
confidence: 54%
“…Regarding the tumor residual pattern in the primary tumor, the dominant pattern in this study was diffuse remnant, followed by shallow remnant, central remnant, and deep remnant. Residual tumor cells were commonly present in adventitia, which is similar to the findings of recent studies on esophageal cancer treated with NCRT, which mostly comprised patients with esophageal adenocarcinoma (28). However, this finding is inconsistent with an observation made in a previous study, which reported that the mucosa and submucosa of the esophageal wall are commonly affected after chemoradiotherapy for esophageal cancer (29).…”
Section: Discussionsupporting
confidence: 54%
“…However, >50% of patients with ESC are diagnosed at a locally advanced stage when the tumor has become inoperable, leaving them with limited management options and a poor prognosis (4,5). Recently, due to the application of multimodality approaches, neoadjuvant therapy has assumed a critical role in ESC management (6)(7)(8)(9)(10)(11). For example, neoadjuvant therapy has achieved a reduction in the tumor burden in patients with unresectable ESC, thereby providing them with the opportunity to undergo surgery (9).…”
Section: Introductionmentioning
confidence: 99%
“…For example, neoadjuvant therapy has achieved a reduction in the tumor burden in patients with unresectable ESC, thereby providing them with the opportunity to undergo surgery (9). Furthermore, neoadjuvant therapy has been shown to improve the R0 resection rate, leaving tumor residues in fewer cases and thereby causing a reduction in the postoperative recurrence of ESC in patients following surgery (10,11).…”
Section: Introductionmentioning
confidence: 99%
“… 1 Although 20–30% of patients achieved a pathologic complete response (pCR), more than half still have residual tumor after nCRT. 2 The tumor microenvironment (TME) is currently a focus in exploring additional treatment combinations. Several potential predictive markers have been evaluated to improve treatment outcome, including the expression of human epidermal growth factor receptor 2 (HER2) and programmed death-ligand 1 (PD-L1), as well as the prevalence of microsatellite instability (MSI).…”
mentioning
confidence: 99%